Architecting noncooperative networks. - Korilis, Y.A.
In noncooperative networks users make control decisions that optimize their individual performance measure. Focusing on routing, two methodologies for architecting noncooperative networks are devised, that improve the overall network performance. These methodologies are motivated by problem settings arising in the provisioning and the run time phases of the network. For either phase, Nash equilibria characterize the operating point of the network. The goal in the provisioning phase is to allocate link capacities that lead to systemwide efficient Nash equilibria. The solution of such design problems is, in general, counterintuitive, since adding link capacity might lead to degradation of user performance. For systems of parallel links, it is shown that such paradoxes cannot occur and that the optimal solution coincides with the solution in the single-user case. Extensions to general network topologies are derived. During the run time phase, a manager controls the routing of part of the network flow. The manager is aware of the noncooperative behavior of the users and makes its routing decisions based on this information while aiming at improving the overall system performance. We obtain necessary and sufficient conditions for enforcing an equilibrium that coincides with the global network optimum, and indicate that these conditions are met in many cases of interest
Keywords: Nash equilibria; Design problems; Global network optimum; Link capacities allocation; Necessary conditions; Network management; Network operating point; Network performance; Network topologies; Noncooperative networks architecture; Optimal solution; Parallel links; Performance measure; Provisioning; Routing; Run time; Sufficient conditions; System performance